2021
DOI: 10.1371/journal.pone.0250839
|View full text |Cite
|
Sign up to set email alerts
|

Validation of protein arginine methyltransferase 5 (PRMT5) as a candidate therapeutic target in the spontaneous canine model of non-Hodgkin lymphoma

Abstract: Non-Hodgkin lymphoma (NHL) is a heterogeneous group of blood cancers arising in lymphoid tissues that commonly effects both humans and dogs. Protein arginine methyltransferase 5 (PRMT5), an enzyme that catalyzes the symmetric di-methylation of arginine residues, is frequently overexpressed and dysregulated in both human solid and hematologic malignancies. In human lymphoma, PRMT5 is a known driver of malignant transformation and oncogenesis, however, the expression and role of PRMT5 in canine lymphoma has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…However, in vivo studies in mice indicated that these drugs did not arrest tumour growth, although the methylation in the target gene promoter was reduced [132]. Sloan et al, (2021) showed an overexpression of protein arginine methyltransferase 5 (PRMT5) in primary B-cell canine lymphomas, arguing that PRMT5 inhibitors could be a candidate as a new therapy in CML [133].…”
Section: Demethylation and Deacetylation Drugs As Treatment For Canin...mentioning
confidence: 99%
“…However, in vivo studies in mice indicated that these drugs did not arrest tumour growth, although the methylation in the target gene promoter was reduced [132]. Sloan et al, (2021) showed an overexpression of protein arginine methyltransferase 5 (PRMT5) in primary B-cell canine lymphomas, arguing that PRMT5 inhibitors could be a candidate as a new therapy in CML [133].…”
Section: Demethylation and Deacetylation Drugs As Treatment For Canin...mentioning
confidence: 99%
“…45 Additionally, in vitro cultured canine lymphoma cells lines that overexpress PRTM5 have increased SDMA and have reductions in intracellular SDMA with PRMT5 inhibition. 43,46,47 To our knowledge, there have been no studies that evaluate both SDMA serum concentrations and concurrent tumour PRMT5 expression in humans, laboratory or pet animals. Further study would be needed to evaluate whether overproduction of SDMA by tumour tissue plays a role in the serum SDMA elevations seen in dogs and cats with lymphoma or other PRMT5 over-expressing tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, over‐expression of PRMT5 in canine lymphoma tissues compared to normal or hyperplastic lymphoid tissue has also been demonstrated 45 . Additionally, in vitro cultured canine lymphoma cells lines that overexpress PRTM5 have increased SDMA and have reductions in intracellular SDMA with PRMT5 inhibition 43,46,47 . To our knowledge, there have been no studies that evaluate both SDMA serum concentrations and concurrent tumour PRMT5 expression in humans, laboratory or pet animals.…”
Section: Discussionmentioning
confidence: 99%
“…We found that PRMT5 knockdown inhibited cell migration and invasion and slowed tumor growth in nude mice. PRMT5 is an emerging epigenetic enzyme that regulates the transcription of target genes through di-methylation of histone residues [ 37 ]. At present, there are highly selective PRMT5 inhibitors developed with PRMT5 as the target, which are used for the treatment of malignant solid tumors and hematological tumors, and have been approved for clinical trials [ 38 ].…”
Section: Discussionmentioning
confidence: 99%